Effect of Blending, Additives and Storage Conditions on the Quality of Watermelon Nectar - Pal, Harshata; Banik, Ashis Kumar; ., Nuchhungi (Journal of Horticultural Sciences, 2007)
The impact of blending of nectar with coconut water, fortification with ascorbic acid and tocopherol and subsequent storage at low temperature (4-5°C) and room temperature (15-33°C) on the quality of nectar was evaluated. In most of the treatments, total soluble solids and reducing sugar content of the nectars increased during storage, whereas the total titratable acidity and lycopene content decreased. Blending and addition of tocopherol did not show improved effect on quality. Low temperature storage recorded better stability.
Keywords: Watermelon Nectar; Total Soluble Solid; Reducing Sugar; Lycopene; Titratable Acidity; Blending; Additives; Storage